Pengaruh Online Advertising, Kreativitas Iklan, dan Daya Tarik Iklan Terhadap Minat Beli Produk Fashion Pada Platform Shopee (Studi pada Mahasiswa di Kota Malang) - Permatasari, Lucy Indah; Wahono, Budi; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to analyze and determine the Influence of Online Advertising, Advertising Creativity and Advertising Attractiveness on Purchase Interest in Fashion Products on the Shopee Platform. This study uses an Explanatory Research type of research with a quantitative approach. Sampling was carried out on students in Malang City who installed the Shopee application using the Malhotra formula so that the sample in this study was 80 respondents. This research method uses multiple linear regression analysis with the SPSS analysis tool. Hypothesis testing uses the t test and F test. The results of this study indicate that Online Advertising, Advertising Creativity and Advertising Attractiveness have a significant simultaneous effect on Purchase Interest in Fashion Products on the Shopee Platform. The variables Online Advertising, Advertising Creativity and Advertising Attractiveness have a significant partial effect on Purchase Interest in Fashion Products on the Shopee Platform. Keywords: Online Advertising, Advertising Creativity, Attraction and Purchase Interest